Analysis of medical records management in Indonesia at selected public hospitals - Hendrawan, Muhammad Rosyihan; Mat Isa, Azman; Samsudin, Ahmad Zam Hariro; Mohd Nordin, Nordiana (Faculty of Information Management, 2025)
Medical records management in Indonesian public hospitals follows uniform guidelines with adjustments to the conditions of each of them. This study aims to analyze the comparative process of medical records management in two public hospitals of different types and classes. Using qualitative descriptive methods, data was collected through interviews, observations, and documentation, then analyzed using an interactive model. The study's findings reveal significant variations in the execution of the medical records lifecycle, stemming from variations in facility ownership, lack of human resources, and the impact of public hospital classification on management quality. Public hospitals with higher classifications tend to have more structured systems and meet standards. These findings underline the importance of improving resources, technology, and governance in medical records management to support hospital accreditation in Indonesia and the quality of health services. Recommendations for further research include a broader assessment of governance and information technology in medical records management.